2016
DOI: 10.3390/foods5040068
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Biscuits Supplemented with Alfalfa Seed Flour

Abstract: The effect of alfalfa seed flour supplementation on the quality characteristics of refined wheat flour-based biscuits was studied. The proximate composition of refined wheat flour and alfalfa seed flour was determined. Refined wheat flour contained 12.43% moisture, 11.52% crude protein, 1.61% crude fat, 0.71% crude fiber, 1.43% ash and 70.83% nitrogen free extract, while alfalfa seed flour contained 5.79%, 29.49%, 12.71%, 5.53%, 4.80% and 41.73% moisture, crude protein, crude fat, crude fiber, ash and nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Ullah et al made biscuits by adding different amounts of alfalfa seed flour to refined wheat flour. They observed that the amount of ash in biscuits changed from 1.37% to 1.92%, respectively [17]. Ash content is in accordance with our results, and their moisture content is higher than the diet biscuits we used in the study.…”
Section: Determination Of Thermal Properties and % Ash Content Of Diet Biscuit Samplessupporting
confidence: 90%
“…Ullah et al made biscuits by adding different amounts of alfalfa seed flour to refined wheat flour. They observed that the amount of ash in biscuits changed from 1.37% to 1.92%, respectively [17]. Ash content is in accordance with our results, and their moisture content is higher than the diet biscuits we used in the study.…”
Section: Determination Of Thermal Properties and % Ash Content Of Diet Biscuit Samplessupporting
confidence: 90%
“…The findings from this study showed that gum Arabic at higher concentrations can be used to increase the crude fibre content of baked products in order for them to be termed as a good source of fibre. Crude fibre content of the biscuits from this study is slightly higher than that of wheat and alfalfa seed flour composite biscuits (0.73-1.62%) as reported by Ullah et al [45]. Eke-Ejiofor et al…”
Section: Effect Of Gum Arabic Incorporation On the Proximate Compositsupporting
confidence: 49%
“…Medicago sativa L. (Leguminosae), commonly called alfalfa, is a perennial herb mostly grown in America, Europe, and Asia [41]. It is used as a source of protein [42,43], fat, and crude fiber [44] and as hay, silage, and pasture [45,46]. Traditionally, its dried leaf is used to lower cholesterol levels [47].…”
Section: Introductionmentioning
confidence: 99%